Between Law and Culture: A Socio-Anthropological Study of Alimony Practices in Contemporary Family Life - M. Zidny Nafi' Hasbi; Nur Syamsiyah binti Ibrahim (Athallah Publishing, 2026)
This study examines the implementation of alimony law within contemporary family life through a socio-anthropological lens, focusing on the interplay between formal legal frameworks and socio-cultural practices. While alimony regulations are designed to ensure post-divorce economic justice, their application often diverges from legal prescriptions due to cultural norms, gender relations, and informal negotiation processes. Using a qualitative approach, this research draws on in-depth interviews, observations, and document analysis to explore how individuals interpret, negotiate, and comply with alimony obligations in everyday life. The findings reveal that alimony practices are not solely determined by legal mandates but are significantly shaped by local values, kinship structures, and power dynamics within families. In many cases, cultural expectations and social pressures either reinforce or undermine formal legal provisions, leading to variations in compliance and enforcement. Additionally, gendered perceptions of responsibility and economic roles play a crucial role in influencing both the willingness to provide and the ability to claim alimony. This study contributes to the literature by highlighting the gap between law in the books and law in action, emphasizing the importance of integrating socio-cultural considerations into legal policy design. It argues that effective implementation of alimony law requires not only institutional enforcement but also culturally sensitive approaches that acknowledge the lived realities of family life.